Cerebral oxygen desaturation events during and functional outcomes after prehospital anaesthesia: A prospective pilot study - Nurmi Jouni; Laukkanen-Nevala Päivi; Kirves Hetti; Raatiniemi Lasse; Toivonen Tuukka; Tommila Miretta; Piiroinen Heini; Setälä Piritta; Karhivuori Pamela; Tukia Simo; Olkinuora Anna (WILEY, 2025)
Background: During prehospital anaesthesia, oxygen delivery to the brain might be inadequate to match the oxygen consumption, with unknown long-term functional outcomes. We aimed to evaluate the feasibility of monitoring cerebral oxygenation during prehospital anaesthesia and determining the long-term outcomes.
Methods: We performed a prospective observational feasibility study in two helicopter emergency medical services units. Frontal lobe regional oxygen saturation (rSO(2)) of adult patients undergoing prehospital anaesthesia was monitored with near-infrared spectroscopy (NIRS) by a Nonin H500 oximeter. The outcome was evaluated with a modified Rankin Scale (mRS) at 30 days and 1 year. Health-related quality of life (HRQoL) was measured with a 15D instrument at 1 year.
Results: Of 101 patients enrolled, 83 were included. The mean baseline rSO(2) was 79% (73-84). Desaturation for at least 5 min to rSO(2) below 50% or a decrease of 10% from baseline occurred in four (5%, 95% CI 2%-12%) and 19 (23%, 95% CI 15-93) patients. At 1 year, 32 patients (53%, 95% CI 41-65) achieved favourable neurological outcomes. The median 15D score was 0.889 (Q1-Q3, 0.796-0.970).
Conclusion: Monitoring cerebral oxygenation with a hand-held oximeter during prehospital anaesthesia and collecting data on functional outcomes and HRQoL are feasible. Only half of the patients achieved a favourable functional outcome. The effects of cerebral oxygenation on outcomes during prehospital critical care need to be assessed in future studies.